Utilization of Dairy Cow Milk For Community Health Empowerment in Cibiru Wetan Village, Bandung Regency - Jafar, Garnadi; Fatmawati, Fenti; Anggraeni, Vina Juliana; Ziska, Rahma; Pasha, ED Yunisa Mega; Susilawati, Elis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
In Cibiru Wetan, Bandung, cows' milk production reaches 5,000 liters per day, but most of it is not absorbed by the cooperative because it does not meet quality standards and is ultimately wasted. This highlights the gap between production potential and post-harvest processing capabilities at the farmer level. Training in processing milk into yogurt using simple technology can reduce waste while also opening up opportunities for public health and local entrepreneurship. The community service activity entitled